Interactions of large T-Antigen (LT) protein of polyomaviruses with p53 unfold their cancerogenic potential. Issue 11 (28th June 2022) - Kellogg, Caroline; Kouznetsova, Valentina L.; Tsigelny, Igor F.
Abstract: Polyomaviruses such as Simian Virus 40 (SV40) and John Cunningham Virus (JCV) have been extensively studied for their potential role in aiding oncogenic transformation. One of the mechanisms through which they do this is by inactivating p53, a known tumor suppressor, through one of their viral proteins, large T-antigen (LT). However, these two viruses represent only a fraction of existing polyomaviruses. Using Clustal Omega, we aligned the protein sequences of LT for 12 different polyomaviruses and found high similarity across polyomavirus LT. We then utilized Molecular Operating Environment (MOE) v2019.01 to compare the binding of SV40 LT to p53 and p53 to DNA to more precisely define the mechanism with which SV40 LT inactivates p53. By binding to p53 residues essential to DNA binding, SV40 LT prevents the proper interaction of p53 with DNA and consequently its fulfillment of transcription factor functions. To further explore the possibility for other polyomavirus LT to do the same, we either retrieved existing 3D structures from RCSB Protein Data Bank or generated 3D homology models of other polyomavirus LT and modeled their interactions with p53. These models interacted with p53 in a similar manner as SV40 LT and provide further evidence of the potential of other polyomavirus LT to inactivate p53. This work demonstrates the importance of investigating the oncogenic potential of polyomaviruses and elucidates future targets for cancer treatment. Communicated by Ramaswamy H. Sarma